Myositis ossificans revisited – The largest reported case series - Saad, A. (J Clin Orthop Trauma, 2021)
INTRODUCTION: Myositis ossificans (MO) is a condition characterised by the formation of non-neoplastic heterotropic ossification in extraskeletal soft tissues. MATERIAL AND METHODS: We performed a retrospective study of our radiology databases within our tertiary orthopaedic centre to identify all cases of MO, reported on X ray, Magnetic resonance imaging (MRI) and Computed tomography (CT) over the past 13 years (2007–2020). RESULTS: We identified 68 cases of MO, which were included into our cohort. The average age of our patients was 36 years (range 4–84 years). 73% of cases (n = 50) were found to affect the lower limb muscles with the majority in the quadriceps. CONCLUSION: We report the largest case series of MO and discuss the demographics, diagnoses and management.